Pain outcomes in patients with advanced breast cancer and bone metastases. Issue 4 (5th September 2012) - Cleeland, Charles S.; Body, Jean‐Jacques; Stopeck, Alison; von Moos, Roger; Fallowfield, Lesley; Mathias, Susan D.; Patrick, Donald L.; Clemons, Mark; Tonkin, Katia; Masuda, Norikazu; Lipton, Allan; de Boer, Richard; et al.
Abstract BACKGROUND: In this study, the authors evaluated the effect of denosumab versus zoledronic acid (ZA) on pain in patients with advanced breast cancer and bone metastases. METHODS: The prevention of pain, reduction in pain interference with daily life activities, and the proportion of patients requiring strong opioid analgesics were assessed in a randomized, double‐blind, double‐dummy phase 3 study comparing denosumab with ZA for preventing skeletal‐related events in 2046 patients who had breast cancer and bone metastases. Patients completed the Brief Pain Inventory‐Short Form at baseline and monthly thereafter. RESULTS: Fewer patients who received denosumab reported a clinically meaningful worsening of pain severity (≥2‐point increase) from baseline compared with patients who received ZA, and a trend was observed toward delayed time to pain worsening with denosumab versus ZA (denosumab, 8.5 months; ZA, 7.4 months; P = .08). In patients who had no/mild pain at baseline, a 4‐month delay in progression to moderate/severe pain was observed with denosumab compared with ZA (9.7 months vs 5.8 months; P = .002). Denosumab delayed the time to increased pain interference by approximately 1 month compared with ZA (denosumab, 16.0 months; ZA, 14.9 months; P = .09). The time to pain improvement (P = .72) and the time to decreased pain interference (P = .92) were similar between the groups. Fewer denosumab‐treated patients reported increased analgesic use from no/low use at baseline to strong opioid use. CONCLUSIONS: Denosumab demonstrated improved pain prevention and comparable pain palliation compared with ZA. In addition, fewer denosumab‐treated patients shifted to strong opioid analgesic use. Cancer 2013. © 2012 American Cancer Society.